Progress of UAV Ad Hoc Network:A Survey - Kun Zhuo; Hengyang Zhang; Bo Zheng; Yunjun Qi (Dianxin kexue)
With the emphasis on effective utilization of UAV of the national interests,the upsurge in multi-UAV cooperative application development and the rapid development of Ad Hoc network application research,UAV Ad Hoc network has become a new hot research area.The basic conception,the main characteristics and the application advantages of the UAV Ad Hoc network were summarized firstly,then a more detailed description of five important research topics of networking technology was given:MAC protocols,routing protocols,transport protocols,cross-1ayer protocols design and opportunistic networks.The development environment of experimental platform of the research organizations on UAV Ad Hoc network were introduced,finally the challenges which encountered in current research and the key issues need to be solved were investigated.